2021
DOI: 10.1111/gcb.15761
|View full text |Cite
|
Sign up to set email alerts
|

Thermal limits in the face of infectious disease: How important are pathogens?

Abstract: The frequency and severity of both extreme thermal events and disease outbreaks are predicted to continue to shift as a consequence of global change. As a result, species persistence will likely be increasingly dependent on the interaction between thermal stress and pathogen exposure. Missing from the intersection between studies of infectious disease and thermal ecology, however, is the capacity for pathogen exposure to directly disrupt a host's ability to cope with thermal stress. Common sources of variation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 131 publications
(261 reference statements)
0
21
0
Order By: Relevance
“…Only 10 studies were found highlighting the general lack of data available. amplifies the risk that many populations face (reviewed in [14,26]). Indeed, infection can alter a host's entire thermal performance curve, shifting lower and upper thermal limits, alongside thermal optima (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Only 10 studies were found highlighting the general lack of data available. amplifies the risk that many populations face (reviewed in [14,26]). Indeed, infection can alter a host's entire thermal performance curve, shifting lower and upper thermal limits, alongside thermal optima (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…2B ) than fundamental TPCs. Even though antagonists (pathogens and competitors) can reduce the thermal performance breadths of animals in the absence of facilitative interactions ( Tsai et al 2020 ; Hector et al 2021 ), the stress-gradient hypothesis suggests that facilitative interactions would overpower these negative effects of antagonists at thermal extremes. Further, because warming often increases drought intensity, facilitative microbes that increase drought tolerance ( Kivlin et al 2013 ) may be more beneficial to plants under future climate change, potentially elevating performance under increasing temperatures relative to a no-microbe control.…”
Section: Future Avenues For Tpcs In Plant Ecology and Evolutionmentioning
confidence: 99%
“…Temperature interacts with a number of other environmental factors to determine performance; or stated differently, the TPC is itself a function of other factors. Food/nutrient availability, pH, light (for photosynthetic organisms), salinity, water availability, oxygen concentration, as well as biotic interactions such as parasitism or mutualism, all can alter the shape of the TPC (Ern et al 2016, Thomas et al 2017, Aldea-Sánchez et al 2021, Hector et al 2021.…”
Section: The Dependence Of Tpcs On Environmental Factorsmentioning
confidence: 99%